Rationalize
the
denominator
Attachments:
![](https://hi-static.z-dn.net/files/dff/e3af0ec7ec2a0f78b5fa91c144195218.jpg)
Answers
Answered by
2
Solution :
For rationalising the denominator we have to Multiply the numerator and denominator by the denominator by changing it's sign .
- (+) changes into (-)
- (-) changes into (+)
= (√3 - √2)/(√3 + √2)
= (√3 - √2) × (√3 - √2)/(√3 + √2) × (√3 - √2)
By using identities :
- (a - b)(a - b) = a² + b² - 2ab
- (a + b)(a - b) = a² - b²
= (√3² + √2² - 2× √3 × √2)/(√3² - √2²)
= (3 + 2 - 2√6)/(3 - 2)
= (5 - 2√6)/1
= (5 - 2√6)
━━━━━━━━━━━━━━━━━━━━━━━━━
Answered by
0
Answer in the attachment
Attachments:
![](https://hi-static.z-dn.net/files/d74/743747332f107432ebea7e1fc7d5b423.jpg)
Similar questions